2013
DOI: 10.1371/journal.pone.0065150
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbon-Induced Signaling Events Relevant to Inflammation and Tumorigenesis in Lung Cells Are Dependent on Molecular Structure

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental and occupational toxicants, which are a major human health concern in the U.S. and abroad. Previous research has focused on the genotoxic events caused by high molecular weight PAHs, but not on non-genotoxic events elicited by low molecular weight PAHs. We used an isomeric pair of low molecular weight PAHs, namely 1-Methylanthracene (1-MeA) and 2-Methylanthracene (2-MeA), in which only 1-MeA possessed a bay-like region, and hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 79 publications
8
79
0
1
Order By: Relevance
“…Among these components of the PM2.5 in our study, Zn, Ni, Al, Pb and PAHs were all reported to activate iNOS directly [28][29][30][31][32], suggesting the direct activation of iNOS by these PM2.5 components. Especially, PAHs were verified to upregulate iNOS expression via the decrease of their DNA methylation level [33][34][35]. Indeed, our results showed that PM2.5 exposure could reduce the DNA methylation of iNOS at 0.5hr, highly supporting the potential role of PAHs in activating iNOS (Fig.…”
Section: The Influence Of Single Exposure To Pm25 On the Level Of Tnsupporting
confidence: 69%
“…Among these components of the PM2.5 in our study, Zn, Ni, Al, Pb and PAHs were all reported to activate iNOS directly [28][29][30][31][32], suggesting the direct activation of iNOS by these PM2.5 components. Especially, PAHs were verified to upregulate iNOS expression via the decrease of their DNA methylation level [33][34][35]. Indeed, our results showed that PM2.5 exposure could reduce the DNA methylation of iNOS at 0.5hr, highly supporting the potential role of PAHs in activating iNOS (Fig.…”
Section: The Influence Of Single Exposure To Pm25 On the Level Of Tnsupporting
confidence: 69%
“…Studies have shown that connexins play a key role in mediating inflammation. For example, inflammation by polycyclic aromatic hydrocarbons in lung and liver epithelial cells results in the inhibition of gap junction intercellular communication through production of arachidonic acid, chemokines, TNF, and Cox-2 activation [17][18][19][20]. In activated peritoneal macrophages, inhibition Cx43 function through either pharmacologic administration or gene knockout improved survival, indicated by a reduction in cytokines during sepsis [21].…”
Section: Introductionmentioning
confidence: 99%
“…The dysregulation of GJIC by VIN was attenuated by an inhibitor of p38, which is mechanistically similar to effects induced by 1-MeA in lung but not liver epithelial cells (Osgood et al, 2013;Upham et al, 2008), or by anisomycin in WB-F344 cells (Ogawa et al, 2004). Interestingly, the effects of MXC and VIN on GJIC were prevented by an inhibitor of PC-PLC.…”
Section: Discussionmentioning
confidence: 57%
“…Also, endogenous or synthetic estrogens and androgens were found to affect GJIC and connexins not only via classical genomic mechanism (Ren et al, 2013), but also via rapid actions of non-genomic signaling (Iwase et al, 2006;Lyng et al, 2000;Pluciennik et al, 1996). GJIC thus represents a cellular event possibly altered by hormones and EDCs via different mechanisms, which might be chemical-, as well as cell type-specific (Osgood et al, 2013;Sovadinova et al, 2015). The immediate cell responses to MXC and VIN observed in this study, such as inhibition of GJIC and phosphorylation of MAPKs and Cx43, were most likely mediated by rapid mechanisms independent of ER or AR genomic signaling.…”
Section: Discussionmentioning
confidence: 99%